The Family Court – Contempt and Inherent Powers - Atkin, Bill (Victoria University of Wellington Law Review, 2023)
This article honours the achievements of Professor ATH Smith both in New Zealand and abroad. Its focus is on aspects of the New Zealand Family Court. The law of contempt is now governed by the Contempt of Court Act 2019. The earlier leading case on the contempt powers of the Family Court is analysed, followed by the changes made by the 2019 Act and their implications for the Court. The discussion is on the basis that the Family Court does not have inherent powers to deal with contempt situations not covered by the statutory scheme. As a part of the District Court, its inherent powers are limited to matters of procedure: contempt is a substantive matter, not one of procedure. The article concludes by briefly raising the wider question of whether the distinction between the senior courts and the lower ones, such as the Family Court, is helpful.